Historical context of the advancement of clinical engineering: An analysis of its implementation and relevance (Research, Society and Development, 2023)
Clinical engineering is an important profession within hospital environments, it was created in 1960 in the United States of America. During this period, there was a great technological development, equipment, exams, monitoring and surgical processes, hence the need to train qualified professionals to provide technical assistance in this equipment. This article aims to analyze the evolutionary process of Clinical Engineering, in its historical context, showing its evolution, as well as its importance in the present day, through a bibliographical review of national and international literature. Methodologically, a deductive approach was taken, which departed from “the various historical contexts of the emergence of clinical engineering”, the research has a bibliographic nature, since it is supported by “an overview of works already carried out so far”, it is still characterized by a qualitative and comparative approach. Several themes and concepts related to the area of clinical engineering were addressed in this work, it was possible to identify and prove that after the insertion of the clinical engineer in the hospital environment, he greatly improved the services. In the United States, clinical engineering followed naturally, initially the safety of the equipment was guaranteed around the 1960s and 1970s, the next act, attempts were made to improve performance and reduce costs in the 1980s and 1990s. due to the delay in the implementation of the profession, it only started to gain strength in the early 90s.